Beetroot Peel Extract as a Natural Preservative for Shelf life Extension of Deccan mahseer (Tor khudree) Steaks during Chill Storage - Maqbool, Hafsa; Safeena, M. P.; Sathish Kumar, K.; Zynudheen, A. A.; Ninan, George; Manoj Kumar, B. (Fishery Technology, 2019)
The efficacy of solvent free beetroot (Beta vulgaris)peel extract in retarding the lipid oxidation ofmahseer steaks were evaluated during chill storage.Preliminary analysis of the beetroot peel extract(BPE) for antioxidant activity were evaluated basedon the total phenolic content, 2, 2-diphenyl-1-picrylhydrazyl radical scavenging activity and 2, 2-azino-bis (3-thylbenzothiazoline-6-sulfonic acid radicalscavenging activity. BPE had total phenoliccontent of 360.47 mg 100 g-1; both DPPH activity(91.62%) and ABTS radical scavenging activity(99.04%) were found to be higher at 20% concentration.Mahseer steaks were given dip treatment inbeetroot peel extract (20%, w/v) then packed inLDPE pouches and kept at 0-2Â°C. The effect of diptreatment on quality changes of steaks were assessedperiodically for biochemical (pH, PV, FFA, TBA,TMA, TVB-N), microbiological (total plate count)and sensory characteristics along with controlsample. The microbial analysis revealed that thecontrol (CT) sample reached to the limit ofacceptability (7.47 log cfu g-1) on 9th day whiletreated sample remained within the limit up to 15thday of storage. Sensory evaluation also showed thedecreasing trend as the storage days increased. Theresults showed that CT sample exceed the acceptablelimits on 9th day of storage, whereas the BPEtreated sample was found to be acceptable up to 15thday indicating the positive role of BPE in shelf life extension of masher steaks under chilled storage (0-2Â°C).